Genome-Wide Association Study of Piglet Uniformity and Farrowing Interval - Wang, Yuan; Ding, Xiangdong; Tan, Zhen; Ning, Chao; Xing, Kai; Yang, Ting; Pan, Yongjie; Sun, Dongxiao; Wang, Chuduan (Frontiers in Genetics, 2017)
Piglet uniformity (PU) and farrowing interval (FI) are important reproductive traits related to production and economic profits in the pig industry. However, the genetic architecture of the longitudinal trends of reproductive traits still remains elusive. Herein, we performed a genome-wide association study (GWAS) to detect potential genetic variation and candidate genes underlying the phenotypic records at different parities for PU and FI in a population of 884 Large White pigs. In total, 12 significant SNPs were detected on SSC1, 3, 4, 9, and 14, which collectively explained 1~1.79% of the phenotypic variance for PU from parity 1 to parity 4, and 2.58~4.11% for FI at different stages. Of these, 7 SNPs were located within 16 QTL regions related to swine reproductive traits. One QTL region was associated with birth body weight (related to PU) and contained the peak SNP MARC0040730, and another was associated with plasma FSH concentration (related to FI) and contained the SNP MARC0031325. Finally, some positional candidate genes for PU and FI were identified because of their roles in prenatal skeletal muscle development, fetal energy substrate, pre-implantation and the expression of mammary gland epithelium. Identification of novel variants and candidate genes will greatly advance our understanding of the genetic mechanisms of PU and FI, and suggest a specific opportunity for improving marker assisted selection or genomic selection in pigs.